EVALUASI SUMATIF PROGRAM PENDIDIKAN DALAM PERSPEKTIF MODEL CIPP (Context, Input, Process, Product) DI UPTD SD NEGERI 2 PANDAN SARI - Yuliani, Rika; Hidayah, Nurul; Suhaimi; Sulistiyana (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2026)
Summative evaluation of educational programs is an essential instrument to ensure school quality and accountability. This study was conducted at UPTD SD Negeri 2 Pandan Sari with the aim of analyzing the effectiveness of its educational program through the lens of the CIPP model (Context, Input, Process, Product). The research employed a qualitative approach, utilizing interviews, observations, and documentation as data collection techniques. The participants included the principal, teachers, and educational staff. The findings indicate that: (1) in terms of context, the program was designed in alignment with the school’s vision and mission; (2) in terms of input, human resources, facilities, and infrastructure adequately supported program implementation; (3) in terms of process, activities were carried out consistently, although documentation practices require improvement; and (4) in terms of product, the program had a positive impact on students’ literacy development, character formation, social skills, and academic achievement. The study concludes that the CIPP model provides a comprehensive evaluation framework and offers a holistic overview of program effectiveness. These findings serve as a foundation for schools to formulate continuous improvement strategies aimed at enhancing educational quality. Keywords: Summative Evaluation; CIPP Model; Educational Program; Elementary School.